2019
DOI: 10.1681/asn.2018121254
|View full text |Cite
|
Sign up to set email alerts
|

Daratumumab in Sensitized Kidney Transplantation: Potentials and Limitations of Experimental and Clinical Use

Abstract: BackgroundDonor-specific antibodies are associated with increased risk of antibody-mediated rejection and decreased allograft survival. Therefore, reducing the risk of these antibodies remains a clinical need in transplantation. Plasma cells are a logical target of therapy given their critical role in antibody production.MethodsTo target plasma cells, we treated sensitized rhesus macaques with daratumumab (anti-CD38 mAb). Before transplant, we sensitized eight macaques with two sequential skin grafts from MHC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 50 publications
1
95
0
Order By: Relevance
“…To date, only subjective clinical reports have been published on the use of CD38 antibodies in desensitization and treatment of AMR. Kwun and colleagues reported the use of daratumumab in desensitization in a heart transplant candidate [69]. Multiple courses of plasmapheresis, high-dose IVIG, and rituximab result in no significant changes in HLA antibody levels (calculated Panel Reactive Antibody score [cPRA] 98%), with deterioration of clinical condition.…”
Section: Solid Organ Transplantationmentioning
confidence: 99%
“…To date, only subjective clinical reports have been published on the use of CD38 antibodies in desensitization and treatment of AMR. Kwun and colleagues reported the use of daratumumab in desensitization in a heart transplant candidate [69]. Multiple courses of plasmapheresis, high-dose IVIG, and rituximab result in no significant changes in HLA antibody levels (calculated Panel Reactive Antibody score [cPRA] 98%), with deterioration of clinical condition.…”
Section: Solid Organ Transplantationmentioning
confidence: 99%
“…In detail, obinutuzumab is able to overcome the low affinity of certain polymorphisms of the FcGamma receptor 3A on effector cells, hence improving antibody-dependent cytotoxicity in a greater proportion of patients. Clinically, obinutuzumab induces more profound and lasting remission, with an almost twofold higher complete response rate in patients treated for indolent nonHodgkin lymphoma [ 15 ] and may also be more efficient than rituximab in autoimmune diseases [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that daratumumab effectively reduced DSAs and modestly prolonged graft survival posttransplant. However, all animals showed rapid antibody rebound and evidence for intense TCMR at month 1 15 …”
Section: Therapeutic Approaches To Treatment Of Amrmentioning
confidence: 96%